ROCK1 Is Associated with Alzheimer’s Disease-Specific Plaques, as well as Enhances Autophagosome Formation But not Autophagic Aβ Clearance - Hu, Yong-Bo; Zou, Yang; Huang, Yue; Zhang, Yong-Fang; Lourenco, Guinevere F.; Chen, Sheng-Di; Halliday, Glenda M.; Wang, Gang; Ren, Ru-Jing (Frontiers in Cellular Neuroscience, 2016)
Alzheimer’s disease (AD) is the most prevalent form of late-life dementia in the population, characterised by amyloid plaque formation and increased tau deposition, which is modulated by Rho-associated coiled-coil kinase 1 (ROCK1). In this study, we further analyse whether ROCK1 regulates the metabolism of amyloid precursor protein (APP). We show that ROCK1 is colocalised with mature Aβ plaques in patients with AD, in that ROCK1 enhances the amyloidogenic pathway, and that ROCK1 mediated autophagy enhances the intracellular buildup of Aβ in a cell model of AD, (confirmed by increased ROCK1 and decreased Beclin 1 protein levels, with neuronal autophagosome accumulation in prefrontal cortex of AD APP/PS1 mouse model). In vitro over-expression of ROCK1 leads to a decrease in Aβ secretion and an increase in the expression of autophagy-related molecules. ROCK1 interacts with Beclin1, an autophagy initiator, and enhances the intracellular accumulation of Aβ. Reciprocally, overexpression of APP/Aβ promotes ROCK1 expression. Our data suggest ROCK1 participates in regulating Aβ secretion, APP shedding and autophagosome accumulation, and that ROCK1, rather than other kinases, is more likely to be a targetable enzyme for AD therapy.